2014
DOI: 10.1002/maco.201407652
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characterization of surface modification for Ti6Al7Nb implants with hydroxyapatite-zirconia nanoparticles synthesis by ultrasound irradiations

Abstract: Ultrasound irradiation is an effective means of obtaining nanoparticles. Hydroxyapatite-zirconia (HA-ZrO 2 ) synthesized by ultrasound irradiation was coated on Ti6Al7Nb implant alloy by electrophoretic deposition. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) were used to evaluate the morphology and composition of HA-ZrO 2 coatings. The electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization curves were used to characterize the corrosion performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The composite HA-ZrO2 coating containing Ag nanoparticles was deposited on the Zr-Ti alloy samples as described next. The ultrasonic irradiation (US) method has been used to generate Ag nanoparticles [55][56][57]. In the first stage, a Sonopuls HD 3200 horn-type reactor (Bandelin, Berlin, Germany) was used to prepare the samples, where the following US conditions were maintained: 20 kHz frequency and 81 µm amplitude of the acoustic wave.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite HA-ZrO2 coating containing Ag nanoparticles was deposited on the Zr-Ti alloy samples as described next. The ultrasonic irradiation (US) method has been used to generate Ag nanoparticles [55][56][57]. In the first stage, a Sonopuls HD 3200 horn-type reactor (Bandelin, Berlin, Germany) was used to prepare the samples, where the following US conditions were maintained: 20 kHz frequency and 81 µm amplitude of the acoustic wave.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…For PLD coating, the HA-ZrO2-Ag solution was calcinated at 675 o C to get crystalline target surface. The depositions were done in a stainless steel vacuum chamber, equipped with a dry pump (Bluffton Motor Works, Bluffon, IN, USA) which ensured 10 -2 torr pressure during film growth (details of the experimental set-up are given in [57]). The HA (Zr, Ag doped) target was placed on a micrometric precision 3D translation stage and moved constantly during deposition.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…Two Ti alloys with different composition (given in wt.%) were used as the substrate material: Ti-6Al-4V and Ti-21Nb-15Ta-6Zr alloys. The layers on both Ti alloys produced by the pulsed layer deposition (PLD) process were obtained from hydroxyapatite-zirconia (HA-ZrO2) synthesized by ultrasound irradiation [32]. A scanning electron microscope (SEM) Tescan VEGA II LMH, equipped with an EDX detector, was employed to visualize the topographical features and obtain elemental analysis of the coated materials as deposited, or following either mechanical or electrochemical testing.…”
Section: Methodsmentioning
confidence: 99%
“…Zirconia (ZrO2) has also been commonly used as reinforcement for many ceramics because of the chemical inertness and excellent mechanical properties. Therefore, it is desirable to combine the advantages of ZrO2 as reinforcement for HA [32].…”
Section: Introductionmentioning
confidence: 99%
“…Rosalbi et al reported that the addition of Nb into Zr metal could improve the stability of oxide films in NaOH solution . It was found that the nanoparticles of HA–ZrO 2 coated on Ti6Al7Nb alloy showed a good corrosion resistance . Nitrided Ti and Ti‐6Al‐4V can also improve their corrosion resistance .…”
Section: Introductionmentioning
confidence: 99%